Hydrologic controls on CO2 chemistry and flux in subtropical lagoonal estuaries of the northwestern Gulf of Mexico. (13th January 2020) - Yao, Hongming; McCutcheon, Melissa R.; Staryk, Cory J.; Hu, Xinping
Abstract : Estuaries are generally considered a source of CO2 to the atmosphere, although with significant uncertainties in magnitude and controlling factors between and within estuaries. We studied four northwestern Gulf of Mexico estuaries that experience extreme hydrologic conditions between April 2014 and February 2017 to determine the role of dry/wet cycle on estuarine CO2 system. Annual air–water CO2 flux ranged from 2.7 to 35.9 mol·C·m −2 ·yr −1 ; CO2 flux declined by approximately an order of magnitude along with declining river discharge. Episodic flooding made CO2 flux differ between dry (−0.7 to 20.9 mmol·C·m −2 ·d −1 ) and wet (11.6–170.0 mmol·C·m –2 ·d –1 ) conditions. During wet condition, increases in dissolved inorganic carbon (DIC) and total alkalinity (TA) significantly elevated CO2 degassing. Furthermore, ventilation of river‐borne CO2 strengthened degassing when estuaries became overwhelmingly river‐dominated. During flood relaxation, all estuaries experienced heightened productivity, evidenced by DIC and TA consumption in the mid‐salinity range (10–30). When prolonged drought led to hypersalinity (>36.5), biogeochemical and evaporative effects enhanced DIC and TA consumption and CO2 degassing. Due to flooding and high wind speeds, these estuaries were a strong CO2 source during spring and summer. Then they transitioned to a weak CO2 source or sink during the fall. Low temperatures further depressed CO2 efflux during winter except when a pulse of freshwater input occurred. This study demonstrates that changes in the hydrologic condition of estuaries, such as dry/wet cycle and river discharge gradient, will greatly alter air–water CO2 flux and estuarine contribution to the global carbon budget.